2018
DOI: 10.3390/polym10080910
|View full text |Cite
|
Sign up to set email alerts
|

Role of PhaC Type I and Type II Enzymes during PHA Biosynthesis

Abstract: PHA synthases (PhaC) are grouped into four classes based on the kinetics and mechanisms of reaction. The grouping of PhaC enzymes into four classes is dependent on substrate specificity, according to the preference in forming short-chain-length (scl) or medium-chain-length (mcl) polymers: Class I, Class III and Class IV produce scl-PHAs depending on propionate, butyrate, valerate and hexanoate precursors, while Class II PhaC synthesize mcl-PHAs based on the alkane (C6 to C14) precursors. PHA synthases of Class… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…It has been reported that class I PHA synthase is a homodimer of PhaC [8]. Class II PHA synthase is mainly found in Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that class I PHA synthase is a homodimer of PhaC [8]. Class II PHA synthase is mainly found in Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…The key enzymes involved in PHA synthesis are PHA synthases, which are a group of heterogeneous enzymes and include PhaC, PhaE, and PhaR that form homodimers, heterodimers, or work concordantly in their active states. These enzymes are currently divided into four categories, Class I, Class II, Class III and Class IV [8]. Class I, III and IV prefer SCL) carbon chain monomers (C3-5) while class II utilizes MCL PHA monomers (C6–14) [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations